2015
DOI: 10.1002/anie.201500453
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Activation by a Nickel NCN‐Pincer Complex featuring a Non‐Innocent N‐Heterocyclic Carbene: Ammine and Amido Complexes in Equilibrium

Abstract: A Ni0‐NCN pincer complex featuring a six‐membered N‐heterocyclic carbene (NHC) central platform and amidine pendant arms was synthesized by deprotonation of its NiII precursor. It retained chloride in the square‐planar coordination sphere of nickel and was expected to be highly susceptible to oxidative addition reactions. The Ni0 complex rapidly activated ammonia at room temperature, in a ligand‐assisted process where the carbene carbon atom played the unprecedented role of proton acceptor. For the first time,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…1 H, 13 C, 31 P, 19 FNMR spectra were recorded at room temperature using aB ruker AVIII 500 MHz or Bruker AVIII HD NanoBay 400 MHz NMR Spectrometer. 31 PNMR chemical shifts were externally referenced to an 85 %s olution of H 3 PO 4 (aq).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H, 13 C, 31 P, 19 FNMR spectra were recorded at room temperature using aB ruker AVIII 500 MHz or Bruker AVIII HD NanoBay 400 MHz NMR Spectrometer. 31 PNMR chemical shifts were externally referenced to an 85 %s olution of H 3 PO 4 (aq).…”
Section: Methodsmentioning
confidence: 99%
“…31 PNMR chemical shifts were externally referenced to an 85 %s olution of H 3 PO 4 (aq). 19 FNMR chemical shifts were externally referenced to CF 3 COOH. Elemental analyses were performed by Elemental analysis Ltd (Devon).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] New routes resulting in the activation of NÀHb onds in ammonia are particularly appealing because of the dearth of transition-metal systems capable of effecting such atransformation [9][10][11][12][13][14][15][16][17][18][19][20][21] and the relevance of N À H activation to an umber of potentially important industrial processes. [22] In addition to these high profile examples,r ecent studies have shown that complexes of phosphorus(III) with distorted geometry can cleave arange of polarized EÀHbonds (E=Oor N).…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21] Therefore,a dvances in main group mediated activation of ammonia are of great interest. [4, 5, 6c-d,24, 26, 27, 30-32] Ther eaction of 1 with ammonia gas (1 atm) results in the quantitative conversion of 1 to anew product, 2 (Scheme 2).…”
mentioning
confidence: 99%